Unwrapping Core–Shell Nanowires into Nanoribbon‐Based Superstructures1. Issue 43 (13th September 2013) - Pevzner, Alexander; Davidi, Guy; Peretz‐Soroka, Hagit; Havivi, Ehud; Barkay, Zahava; Popovitz‐Biro, Ronit; Khatchtourints, Artium; Patolsky, Fernando
<x xml:space="preserve">Abstract</x> A prize for the ribbons: High‐quality crystalline semiconducting nanoribbons can be prepared by "unwrapping" core–shell nanowire precursors. For example, Ge nanowires were coated with a Si shell and the top surface was carved by etching whereas the sides were protected by a thin layer of photoresist material. Finally the Ge core was removed selectively by chemical means to give fully opened and flat nanoribbon structures (see picture).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>